The Effectiveness of Play Therapy in Improving Attention and Working Memory in Students with Specific Learning Disorders - Mozhgan Etemadzadeh; Farzaneh Hooman; Behnam Makvandi (Shiraz University of Medical Sciences, 2023)
Background: One of the most prominent challenges faced by students with learning disorders is attention and working memory deficits. This study aimed to investigate the effectiveness of play therapy in improving attention and working memory in students with specific learning disorders.Methods: The study employed a quasi-experimental design with pre-test and post-test measurements, including a control group. The statistical population consisted of all fourth-grade students with specific learning disorders in Dezful, Iran, in 2022. Thirty students were purposively selected and allocated to either an experimental or control group, with 15 participants in each group. The experimental group received play therapy sessions (ten 90-minute sessions and one session per week), while the control group received no intervention. The Test of Variables of Attention (TOVA) and the Working Memory Test Battery for Children (WMTB-C) were used for data collection. The analysis of covariance was used to analyze the data via SPSS version 26.Results: The study included 30 students with specific learning disorders, aged 10.24±2.26 years. In the pre-test stage, the experimental group's mean scores for central executive, visual-spatial sketchpad, and phonological loop were 59.47±2.03, 44.80±3.21, and 64.27±1.62, respectively. In the post-test stage, these means increased to 71.87±3.24, 59.87±2.97, and 78.73±2.93, respectively. Furthermore, the experimental group's mean attention scores increased from 69.53±16.81 in the pretest stage to 84.93±14.35 in the post-test stage. The findings indicated that play therapy was effective in improving the attention and working memory of students with specific learning disorders (P<0.001).Conclusion: The results suggested that play therapy can be an effective intervention for improving academic achievement by enhancing attention and working memory in students with specific learning disorders.